Vpliv tlačnih utripanj v sesalni cevi na dinamiko kavitacijskega vrtinca v francisovi turbini - Hočevar, Marko (Strojniški vestnik, 2003)
The influence of pressure pulsations on the cavitation-vortex dynamics in a Francis-turbine draft tube is presented. The experiment was performed on a model Francis turbine in which pressure pulsations on the draft-tube wall and the cavitation-vortex dynamics were acquired simultaneously. The cavitation-vortex dynamics was recorded using a visualization method. An experimental model was proposed in which the cavitation-vortex dynamics was predicted based on recorded pressure information at one point on the draft-tube wall. The performance of the model is, on average, very good. The prediction of the cavitation-vortex dynamics shows better results when the distance between the pressure sensor and the cavitation vortex is short.
Keywords: turbine Francis; vrtinci kavitacijski; utripanja tlačna; vizualizacija; Francisove turbine; kavitacija